Growth Rate in Childhood and Adolescence and the Risk of Breast and Prostate Cancer: A Population-Based Study. Issue 2 (13th October 2021) - Haraldsdottir, Alfheidur; Steingrimsdottir, Laufey; Maskarinec, Gertraud; Adami, Hans-Olov; Aspelund, Thor; Valdimarsdottir, Unnur A; Bjarnason, Ragnar; Thorsdottir, Inga; Halldorsson, Thorhallur I; Gunnarsdottir, Ingibjorg; Tryggvadottir, Laufey; Gudnason, Vilmundur; et al.
Abstract: Growth rate is regulated by hormonal pathways that might affect early cancer development. We explored the association between rate of growth in height from ages 8 to 13 years (childhood) and from age 13 to attainment of adult height (adolescence), as measured at study entry, and the risk of breast or prostate cancer. Participants were 2, 037 Icelanders born during 1915–1935, who took part in the Reykjavik Study, established in 1967. Height measurements were obtained from school records and at study entry. We used multivariable Cox regression models to calculate hazard ratios with 95% confidence intervals of breast and prostate cancer by rates of growth in tertiles. During a mean follow-up of 66 years (women) and 64 years (men), 117 women were diagnosed with breast cancer and 118 men with prostate cancer (45 with advanced disease). Women in the highest growth-rate tertile in adolescence had a higher risk of breast cancer (hazard ratio = 2.4, 95% confidence interval: 1.3, 4.3) compared with women in the lowest tertile. A suggestive inverse association was observed for highest adolescent growth rate in men and advanced prostate cancer: hazard ratio = 0.4, 95% confidence interval: 0.2, 1.0. Rapid growth, particularly in adolescence may affect cancer risk later in life.